Mechanical properties of sustainable concrete containing local ternary blended cement as cement replacement - Nabilla, Mohamad; Khairunisa, Muthusamy; Sofia Adibah, Jasni; Fahrizal, Zulkarnain (Penerbit UTHM, 2024)
Continuous harvesting of limestone for cement production is increasing to cater to the demand of the construction sector and devastate the natural world. The disposal of shells from the local cockle trade also pollutes the environment. Simultaneously, increasing coal bottom ash (CBA) disposal from the rising consumption of coal in power plants raises severe environmental concerns. The discovery of coal bottom ash as pozzolanic ash that can be utilized as partial cement replacement has paved the way for further exploration. However, the concrete’s performance produced using coal bottom ash combined with cockle shell ash (CSA) blended cement has not been reported. This research examines the impact of CBA in CSA blended cement on the mechanical and fresh characteristic of concrete as a cement replacement purposes. Various percentages of CBA as partial cement replacement were integrated into cockle shell ash blended cement concrete. CSA blended cement concrete containing 10% CBA exhibits the highest strength. The utilization of cement formed through the combination of coal bottom ash and cockle shell ash contribute towards the invention of sustainable green concrete with a lesser burden on natural resources and cutting down waste accumulation at the landfill.